2022
DOI: 10.3390/ijerph191912088
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change Risks on Residential Consumption in China: Evidence from ARMAX Modeling and Granger Causality Analysis

Abstract: Estimating the impact of climate change risks on residential consumption is one of the important elements of climate risk management, but there is too little research on it. This paper investigates the impact of climate change risks on residential consumption and the heterogeneous effects of different climate risk types in China by an ARMAX model and examines the Granger causality between them. Empirical results based on monthly data from January 2016 to January 2019 suggest a significant positive effect of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Moreover, climate risks are intertwined with supply chains, Ren et al (2024) found Improving the independence of local resources can help alleviate the impact of global supply chain disruptions. Recent research has also found that the impact of climate change on consumer behavior in China is mainly driven by droughts, floods, and high temperatures, rather than factors such as typhoons and freezing temperatures (Niu and Li, 2022). Furthermore, Hu et al (2023) demonstrated a positive correlation between agricultural carbon emissions and medical expenditures among rural residents.…”
Section: Climate Riskmentioning
confidence: 99%
“…Moreover, climate risks are intertwined with supply chains, Ren et al (2024) found Improving the independence of local resources can help alleviate the impact of global supply chain disruptions. Recent research has also found that the impact of climate change on consumer behavior in China is mainly driven by droughts, floods, and high temperatures, rather than factors such as typhoons and freezing temperatures (Niu and Li, 2022). Furthermore, Hu et al (2023) demonstrated a positive correlation between agricultural carbon emissions and medical expenditures among rural residents.…”
Section: Climate Riskmentioning
confidence: 99%